RELEVANSI PENDEKATAN PEMBELAJARAN TEMATIK INTEGRATIF DI SD/MI DENGAN KONSEP MADRASAH/SEKOLAH RAMAH ANAK - Isna Nurul Inayati; Rima Trianingsih (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
Thematic learning approaches have been implemented since the KTSP curriculum was established in 2006. The implementation of thematic learning approaches then undergone improvements in the 2013 curriculum. Thematic learning approaches that were originally applied using web models or netted, were refined into integrated or integrated models. An integrative thematic model was chosen because it was predicted to be able to accommodate and touch in an integrated manner all the emotional, physical, and academic dimensions of SD / MI students both in the classroom or in the school environment. The implementation of an integrative thematic approach in learning opens up opportunities for teachers to develop the most appropriate strategies and methodologies. Teachers are required to be more creative in presenting a learning atmosphere that leads students to be able to understand the reality of life they live every day, in other words, integrative thematic learning models are relevant to accommodate differences in individual characteristics and learning environments of students. The superiority of the integrative thematic learning model described above basically corresponds to the child-friendly school/madrasah model which is jurisdictionally regulated in the Regulation of the State Minister for Women's Empowerment and Child Protection Number 8 of 2014. To analyze the relevance of integrative thematic learning models with school models child friendly, this study needs to be done Keywords: Integrative Thematic, Child-Friendly School